Path Analysis on Factors Affecting the Quality of Life in Patients with Type 2 Diabetes Mellitus in Surakarta, Central Java - Devi Marlina; Didik Gunawan Tamtomo; RB. Soemanto (Masters Program in Public Health, 2020)
Background: Diabetes mellitus is a chronic disease that cannot be cured entirely, which greatly affects the quality of life. People with dia